Characterization of Solid-State Drug Polymorphs and Real-Time Evaluation of Crystallization Process Consistency by Near-Infrared Spectroscopy - Qi, Shu-Ye; Tian, Ye; Zou, Wen-Bo; Hu, Chang-Qin (Frontiers in Chemistry, 2018)
Herein, we aimed to develop a strategy for evaluating the consistency of pharmaceutically important crystallization processes in real time, focusing on two typical cases of polymorphism. Theoretical analysis using a combination of 13C solid-state nuclear magnetic resonance spectroscopy with other polymorphism analysis techniques identified a number of marker signals, the changes of which revealed the presence of two or more structural orientations (lattices and/or molecular conformations) in both cefazolin sodium pentahydrate (α-CEZ-Na) and cephathiamidine (CETD). The proportions of these forms were shown to be batch-dependent and were defined as critical quality attributes (CQAs) to evaluate process consistency. Subsequently, real-time analysis by chemometrics-assisted near-infrared spectroscopy (NIR) was used to obtain useful information corresponding to CQAs. The pretreated spectra of representative samples were transformed by first derivative and vector normalization methods and used to calculate standard deviations at each wavelength and thus detect significant differences. As a result, vibrational responses of H2O, CH3, and CH2 moieties (at 5280, 4431, and 4339 cm–1, respectively) were shown to be sensitive to the CQAs of α-CEZ-Na, which allowed us to establish a highly accurate discrimination model. Moreover, signals of H2O, CONH, and COOH moieties (at 5211, 5284 and 5369 cm–1, respectively) played the same role in the case of CETD, as confirmed by theoretical results. Thus, we established a technique for the rapid evaluation of crystallization process consistency and deepened our understanding of crystallization behavior by using NIR in combination with polymorphism analysis techniques.